2009
DOI: 10.1007/s10162-009-0187-6
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Incomplete Adaptation to a Severely Shifted Frequency-to-Electrode Mapping by Cochlear Implant Users

Abstract: In the present study, a computational model of phoneme identification was applied to data from a previous study, wherein cochlear implant (CI) users' adaption to a severely shifted frequency allocation map was assessed regularly over 3 months of continual use. This map provided more input filters below 1 kHz, but at the expense of introducing a downwards frequency shift of up to one octave in relation to the CI subjects' clinical maps. At the end of the 3-month study period, it was unclear whether subjects' as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 21 publications
1
51
0
Order By: Relevance
“…The contribution of a nonzero response bias to lowering vowel percent correct scores for the type of frequency mismatch imposed by FAT No. 1 is addressed in Sagi et al, ͑2010͒ wherein the MPI model was applied to the vowel data of Fu et al ͑2002͒.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of a nonzero response bias to lowering vowel percent correct scores for the type of frequency mismatch imposed by FAT No. 1 is addressed in Sagi et al, ͑2010͒ wherein the MPI model was applied to the vowel data of Fu et al ͑2002͒.…”
Section: Discussionmentioning
confidence: 99%
“…The model employed in the present study is an application of the multidimensional phoneme identification (MPI) model (Svirsky, 2000(Svirsky, , 2002Svirsky et al, 2001;Sagi et al, 2010aSagi et al, , 2010b which is a general framework that predicts phoneme identification based on listeners' ability to discriminate speech cues. These speech cues are combined to form a multidimensional perceptual space so that a phoneme's location within the space is defined by that phoneme's set of speech cue values.…”
Section: Introductionmentioning
confidence: 99%
“…Başkent and Shannon (2005) conducted a frequency mapping study 17 with MED-EL C40+ cochlear implant users and simulated different insertion depths. 18 They found that, for simulated insertions between 20 and 25 mm, a reduced frequency 19 range map with less spectral distortion resulted in better speech recognition.…”
mentioning
confidence: 99%
“…Svirsky et al 2 (2004) found that for three post-lingually deafened adults, acclimatization for vowels 3 had occurred after one day, one month and three months post activation respectively, 4 but for a pre-lingually deafened adult, up to 24 months was needed for acclimatization 5 to occur. Sagi et al (2010) reported that some acclimatization occurred following a 6 severe basal spectral shift, for three CI users who were exposed to a shifted map for 7 three months; two could shift their internal representations to the new sound within 8 one week but one had not completely shifted their representation after three months. 9 10 In summary, it is possible that a frequency allocation matched to the CI recipient's 11 internal frequency map, or one adjusted to make best use of remaining spiral ganglion 12 cells, may offer better speech perception than a default map, which maps the speech 13 frequency range (100 -8500 Hz) to the available electrodes.…”
mentioning
confidence: 99%
See 1 more Smart Citation